Outcome of Manipulation under Anesthesia in Treatment of Frozen Shoulder with and without Steroid Injection in Terms of Range of Motion (Medical Forum Monthly, 2024)
Objective: This study was conducted to compare the mean difference in the range of motion (ROM) between manipulation under anesthesia (MUA) with and without intra-articular injection of steroid in patients of Frozen Shoulder (FS).Design: Randomized controlled trial study.Duration and Place: This study was conducted at the Orthopedic Department, BV Hospital Bahawalpur from May 15th, 2016 to October 14th, 2017Materials & Methods: A total of 156 patients of 30 to 75 years of age with FS were included in the study. Patients with metabolic bone disease and osteoporosis were excluded. Pre-operative measurements of the ROM (flexion, abduction, external rotation and internal rotation) of FS were taken in all patients. Selected patients were placed randomly into 2 groups i.e. Group A (MUA without steroid) & Group B (MUA with steroid), by using lottery method.Results: The mean age of women in group A was 55.65 ± 8.13years and in group B was 55.23 ± 8.26years. Out of these 156 patients, 36.54% were male and 63.46% were females with ratio of 1:1.74. Post-manipulation, the results have shown that there was significant improvement (p-value<0.05) in ROM in group B (MUA with steroid injection) compared to group A (MUA without steroid injection).Conclusion: In combined treatment (MUA with steroid injection) ROM is significantly improve as compared to in single treatment (MUA) in FS.